Empowering Women through Education by Implementing Gender-Responsive and Transformative Pedagogies - Leo Christopher Clark (PT. Islamic Research Publisher, 2025)
This study explores the empowerment of women through education by implementing gender-responsive and transformative pedagogies. The primary objective is to examine how integrating pedagogical approaches that are sensitive to gender equity and promote critical thinking can enhance women’s agency, self-confidence, and participation in both academic and social spheres. The research employs a qualitative case study design, involving 30 female students and 10 educators from diverse educational contexts. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed thematically to identify patterns and insights related to gender-sensitive teaching practices. The findings indicate that gender-responsive pedagogies contribute to creating inclusive learning environments where women feel recognized, valued, and supported. Meanwhile, transformative pedagogies encourage critical reflection, dialogue, and active participation, enabling students to challenge existing gender norms and expand their decision-making capacities in personal, academic, and community settings. The study demonstrates that combining these pedagogical approaches not only enhances learning outcomes but also fosters social consciousness and empowerment among women. This research contributes to the existing literature by providing empirical evidence on the practical implementation of gender-responsive and transformative teaching methods. It highlights effective strategies for educators and policymakers aiming to promote gender equity in education, offering insights into curriculum design, classroom management, and teacher training. The study underscores the critical role of pedagogical innovation in empowering women, promoting social transformation, and addressing structural inequalities, thereby advancing both theoretical understanding and practical application of gender-sensitive education in contemporary educational settings.